Implementing tokenization in clinical research to expand real-world insights - Walters, Chelsea; Langlais, Crystal S.; Oakkar, Eva E.; Hoogendoorn, Wilhelmina E.; Coutcher, James B.; Van Zandt, Mui (Frontiers in Drug Safety and Regulation, 2025)
Interest in leveraging real-world data (RWD) to support clinical research is increasing, including studies to further characterize safety and effectiveness of new treatments. Such studies often require a combination of primary, study-specific data, with secondary, existing RWD. So-called enriched studies are becoming more common but require tailored methodologies that facilitate linkage across data sources. Tokenization has emerged as a key tool in the United States (US) to enable the linkage of secondary data with primary data, although key considerations to operationalize tokenization are often overlooked during study set-up. This article aims to explore key aspects for implementing tokenization in the US and to define relevant terminology. Appropriate study designs and RWD sources to leverage this tool are also discussed and advantages and considerations for study stakeholders to enhance possibilities to generate real-world evidence are highlighted. The article concludes with a description of case studies where tokenization is a suitable fit to fulfill study goals.